The Changes in the Policy of Access to the Documents of the Institute of National Remembrance in the Open Government Era in the Context of the Protection of Personal and Sensitive Data (Atlanti, 2016)
This paper is going to present the changes in the policy of access to the documents of the Institute of National Remembrance in the period from 2000 until this day in the context of the protection of personal and sensitive data. The paper aims to show the extent to which the policy of access binding in the IPN applies to the guidelines established by the International Council on Archives. To that end, the provisions of access in the IPN have been compared with the Principles of Access to Archives prepared by the ICA. The outline of the changes in the policy of access presented in the paper on the basis on the Act on the Institute of National Remembrance an the Act on the Disclosure of Information confirms unquestionably that the IPN managed successfully to adjust to the Principles and to meet the requirements of the ICA.
Keywords: access; Institute of National Remembrance; personal data; sensitive data; principles of access